Two hundred and five newly assembled mitogenomes provide mixed evidence for rivers as drivers of speciation for Amazonian primates. Issue 14 (20th June 2022) - Janiak, Mareike C.; Silva, Felipe E.; Beck, Robin M. D.; de Vries, Dorien; Kuderna, Lukas F. K.; Torosin, Nicole S.; Melin, Amanda D.; Marquès‐Bonet, Tomàs; Goodhead, Ian B.; Messias, Mariluce; da Silva, Maria N. F.; Sampaio, Iracilda; et al.
Abstract: Mitochondrial DNA remains a cornerstone for molecular ecology, especially for study species from which high‐quality tissue samples cannot be easily obtained. Methods using mitochondrial markers are usually reliant on reference databases, but these are often incomplete. Furthermore, available mitochondrial genomes often lack crucial metadata, such as sampling location, limiting their utility for many analyses. Here, we assembled 205 new mitochondrial genomes for platyrrhine primates, most from the Amazon and with known sampling locations. We present a dated mitogenomic phylogeny based on these samples along with additional published platyrrhine mitogenomes, and use this to assess support for the long‐standing riverine barrier hypothesis (RBH), which proposes that river formation was a major driver of speciation in Amazonian primates. Along the Amazon, Negro, and Madeira rivers, we found mixed support for the RBH. While we identified divergences that coincide with a river barrier, only some occur synchronously and also overlap with the proposed dates of river formation. The most compelling evidence is for the Amazon river potentially driving speciation within bearded saki monkeys ( Chiropotes spp.) and within the smallest extant platyrrhines, the marmosets and tamarins. However, we also found that even large rivers do not appear to be barriers for some primates, including howler monkeys ( Alouatta spp.), uakaris ( Cacajao spp.), sakis ( Pithecia spp.), and robust capuchins ( Sapajus spp.). Our results support a more nuanced, clade‐specific effect of riverine barriers and suggest that other evolutionary mechanisms, besides the RBH and allopatric speciation, may have played an important role in the diversification of platyrrhines.